Analisis Perubahan Makna dalam Bahasa Indonesia Kontemporer di Media Sosial - Agus Jayadi (Journal of Language Studies, 2025)
This study investigates semantic shifts in contemporary Indonesian as observed in social media platforms. With the rapid growth of digital communication, language use has become increasingly dynamic, leading to notable changes in word meanings. The research aims to identify common lexical items that have undergone semantic change, classify the types of shifts (e.g., broadening, narrowing, amelioration, pejoration, and metaphorical extension), and analyze the sociolinguistic factors influencing these changes. Data were collected from Twitter, Instagram, and TikTok through purposive sampling of posts from 2020 to 2024. Qualitative analysis was conducted using a descriptive-semantic approach. The findings reveal that semantic change in Indonesian on social media is driven by youth subcultures, pop culture references, meme culture, and the need for concise and expressive communication. This study contributes to the understanding of contemporary language dynamics and highlights the role of social media as a catalyst for linguistic innovation in Indonesian.